The International Dimension of EU Competition Law and Policy / [electronic resource] - Papadopoulos, Anestis S. (Cambridge : Cambridge University Press, 2010)
Modern competition law was first employed by countries over one hundred years ago in order to address issues relating to restrictions of trade at the national level. Recent international economic integration has weakened the distinction between the domestic and the international in several fields of economic activity, and consequently the laws which regulate such activity, competition law included. Several attempts to address the paradox of adopting national competition rules to address international issues have been made at the international, regional and (lately) bilateral levels. This book discusses the international dimension of EU competition law, and examines the position taken by the EU in four distinct categories of international agreements which are devoted to competition or include competition provisions. In particular, it analyses the EU's position with regard to bilateral enforcement cooperation agreements, bilateral free trade agreements, plurilateral-regional agreements and the long negotiations for the adoption of a multilateral competition regime.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Restaint of trade; Antitrust law